Modeling and Performance Analysis of 3D Structured Rectilinear Rogowski Coil Using Finite Element Method - Bawankule, Priti; Chandrasekaran, Kandasamy (Periodica polytechnica. Electrical engineering and computer science, 2025)
This paper proposed a discrete Rogowski coil (RC) model, consist of rectilinear solenoids (S) connected in series. This model is designed using ANSYS Maxwell software for different shape of primary conductor and the mutual inductance (M) between RC model are calculated. The paper discussed about impact of various shape and different position of primary conductor. The M between the RC model and straight circular, rectangular cross section and D-shaped conductors are evaluated using the Finite Element Method (FEM). The effect of cross section of primary conductor on M has analyzed and reported. For larger numbers of S, eccentricity of conductor will decrease so that output of coil is also improved. In this study, the distribution of magnetic field is examined for changes in the position of the conductors. The designed RC model output is studied with respect to the power and high frequency input signals. A discrete RC is tested using simulated standard sinusoidal and impulse (8/20 μs) as an input signal. Performance of the RC is analyzed, and its results for the different input magnitude is reported. An output characteristic and sensitivity of the designed RC have also been determined and reported.